2009
DOI: 10.1111/j.1399-5448.2008.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved metabolic outcome in a Danish diabetic paediatric population aged 0-18 yr: results from a nationwide continuous Registration

Abstract: The objective of the present study was to describe the changes in glycaemic control based on data from the nationwide Danish Registry of Childhood Diabetes with valid haemoglobin A1c (HbA1c) readings centrally analysed between 1996 and 2006. The glycaemic control was assessed using generalized linear mixed models. Centre, age, diabetes duration, ethnicity, sex, self-monitoring of blood glucose, insulin regimens and hypoglycaemia was tested as explanatory variables. There were 9291 HbA1c recordings from 2705 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
67
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 24 publications
13
67
1
Order By: Relevance
“…In 2008 a follow-up study from the Danish Registry of Diabetes in Childhood and Adolescents demonstrated that the mean HbA 1c level decreased from 9.0% (95% CI AE 0.82) (75 mmol/mol) to 8.2% (95% CI AE 0.06) (66 mmol/mol) in the period from 1997 to 2006 [1]. The reason for this decrease is unknown.…”
Section: Introductionmentioning
confidence: 86%
“…In 2008 a follow-up study from the Danish Registry of Diabetes in Childhood and Adolescents demonstrated that the mean HbA 1c level decreased from 9.0% (95% CI AE 0.82) (75 mmol/mol) to 8.2% (95% CI AE 0.06) (66 mmol/mol) in the period from 1997 to 2006 [1]. The reason for this decrease is unknown.…”
Section: Introductionmentioning
confidence: 86%
“…The register collects clinical information on the registrees annually, and has a biobank associated with it, where DNA and serum samples (conditional on consent) are collected from new cases and first-degree relatives. It is considered 100% valid and is therefore a valuable source for epidemiological studies but also for clinical and biological studies [4] because of the biobank material available. As the register is clinically based there is no link to the NDR.…”
Section: Other Diabetes Registersmentioning
confidence: 99%
“…130,133 Quality control To investigate outcomes of care in infant-onset diabetes mellitus, prospective data systems have been established by national networks. [134][135][136] Major differences in metabolic outcome have been demonstrated between international pediatric diabetes centers. 137 Including more than 38,000 children with diabetes aged 0-18 years, the prospective diabetes documentation initiative (DPV), which contains data from Germany and Austria, is one of the largest data documentation systems for childhood diabetes mellitus worldwide.…”
Section: Ongoing Diabetes Carementioning
confidence: 99%